1995
DOI: 10.1143/ptps.118.1
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Highest Weight Modules of the Elliptic Algebra $\mathfrak{A}_{q, p}(\hat{sl_2})$

Abstract: We discuss a construction of highest weight modules for the recently defined elliptic algebra A q,p ( sl 2 ), and make several conjectures concerning them. The modules are generated by the action of the components of the operator L on the highest weight vectors. We introduce the vertex operators Φ and Ψ * through their commutation relations with the L-operator. We present ordering rules for the Land Φ-operators and find an upper bound for the number of linearly independent vectors generated by them, which agre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 17 publications
2
57
0
Order By: Relevance
“…(As for the definition of the intertwiner Φ(ζ), see [5,6] and [1].) More precisely, in [1] the matrix elements Φ(ζ 1 )Φ(ζ 2 ) · · · Φ(ζ n ) were represented by applying the n-fold integral transformation to a basic hypergeometric series.…”
Section: Introductionmentioning
confidence: 99%
“…(As for the definition of the intertwiner Φ(ζ), see [5,6] and [1].) More precisely, in [1] the matrix elements Φ(ζ 1 )Φ(ζ 2 ) · · · Φ(ζ n ) were represented by applying the n-fold integral transformation to a basic hypergeometric series.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we remind the reader of the fact that in the trigonometric case, i.e. U q ( sl N ), the L-operator can be constructed as a composition of type I and II vertex operators [17,18]. The following theorem is an elliptic analogue of such a construction.…”
Section: Theorem 64mentioning
confidence: 99%
“…We thus give a representation theoretical meaning to the vertex operators of the A N −1 type face model [16]. Conversely, as a composition of the type I and type II intertwiners, one can construct a L-operator which satisfies the RLL-relations [17,18]. As a check of our free field realization, we investigate a connection between the two L-operators, the one constructed by a composition of the vertex operators and the other by the half currents, in the level-one representation.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations along this line showed that there are several kinds of elliptic quantum groups [7,8,9,10,11,12,14,15,18,21], some are recognized as quasi-triangular quasi-Hopf algebras and some are still not. Due to the lack of co-algebraic structures for some of the elliptic…”
Section: Introductionmentioning
confidence: 99%
“…From a pure mathematical point of view, the most important significance for the discovery of elliptic quantum groups might be that it reveals the possibility for the existence of non-co-associative and non-commutative non-co-commutative associative algebras. Such algebras also happen to describe the dynamical symmetry of some statistical models and hence greatly attracted the attention of theoretical physicists.Further investigations along this line showed that there are several kinds of elliptic quantum groups [7,8,9,10,11,12,14,15,18,21], some are recognized as quasi-triangular quasi-Hopf algebras and some are still not. Due to the lack of co-algebraic structures for some of the elliptic…”
mentioning
confidence: 99%